Militant democracy and successors to authoritarian ruling parties in post-1945 West Germany and Italy. Issue 4 (19th May 2022) - Bourne, Angela; Veugelers, John
ABSTRACT: This article contributes to the empirical literature on militant democracy and successor party bans by comparing post-1945 West Germany and Italy. These countries shared a right-authoritarian past but their tolerance of right-authoritarian parties differed. Looking for reasons behind the ban of the Sozialistische Reichspartei Deutschlands and the survival of the Movimento sociale italiano, this study tests five conditions: (1) ambiguity towards – if not open approval of – violence; (2) absence of effective alternatives to proscription; (3) securitization; (4) veto player agreement; (5) veto player incentives. We find that securitization is a necessary condition for proscription, whereas approval of violence is not. While neither the presence of effective alternatives nor veto player incentives relate to ban outcomes in a consistent pattern, veto player support remains crucial. Given the findings from this comparative study, we conclude that successor party bans should not belong to a separate category of militant democracy.